Perkembangan Pendidikan Islam di Madrasah: Tinjauan Sejarah, Kurikulum, Peran, dan Tantangan : Penelitian - Juli Azmi; Abdusima Nasution; Salman Thoat; Annisa Hilda Panjaitan; Rika Andriyani Ritonga; Amron Hasibuan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Madrasah as an Islamic educational institution has a strategic role in the formation of character and morals of students. This study aims to analyze the development of madrasahs in Indonesia from the aspects of history, curriculum, roles, and challenges faced. The research method used is a literature study by collecting data from various sources such as books, journals, and education policy documents. The results of the study indicate that madrasahs have evolved from traditional mosque-based institutions to formal institutions recognized in the national education system. The madrasah curriculum combines general and religious education with a portion of 40% religious material. Madrasahs play an important role in instilling Islamic values ​​through teacher role models, worship practices, and religious environments. However, madrasahs still face challenges such as limited facilities, technological gaps, and complicated bureaucracy. The solutions offered include increasing government support, strengthening the curriculum, and optimizing madrasah management. This study provides recommendations for policy makers to strengthen the role of madrasahs in the national education system.